2012
DOI: 10.1121/1.3675002
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity driven ultrasound imaging

Abstract: An image formation framework for ultrasound imaging from synthetic transducer arrays based on sparsity-driven regularization functionals using single-frequency Fourier domain data is proposed. The framework involves the use of a physics-based forward model of the ultrasound observation process, the formulation of image formation as the solution of an associated optimization problem, and the solution of that problem through efficient numerical algorithms. The sparsity-driven, model-based approach estimates a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…While fluctuation-based approaches eliminate the need for isolating individual sources, they remain limited in terms of spatial resolution improvement and temporal resolution. It was also shown that model-based reconstruction with sparsity constraints on the sample, an approach originating from the field of compressed sensing 9 , could yield super-resolved US 30,31 and PA 32 images. A major advantage of model-based reconstruction over the previously mentioned localization-based and fluctuation-based techniques is that by requiring (in principle) only a single-shot acquisition it permits a high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…While fluctuation-based approaches eliminate the need for isolating individual sources, they remain limited in terms of spatial resolution improvement and temporal resolution. It was also shown that model-based reconstruction with sparsity constraints on the sample, an approach originating from the field of compressed sensing 9 , could yield super-resolved US 30,31 and PA 32 images. A major advantage of model-based reconstruction over the previously mentioned localization-based and fluctuation-based techniques is that by requiring (in principle) only a single-shot acquisition it permits a high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The regularization parameter λ balances the first term and second term of Equation (2), which means the value is affected by the fidelity of the measurements, the noise level, and the sparse level of the image [26]. For a given C-scan image, a large value will result in a least squares solution which may be unstable, while a small value may over smooth the solution due to excessive regularization [18,26,27,28]. Here, we set λ according to the method described in [28].…”
Section: Methodsmentioning
confidence: 99%
“…For a given C-scan image, a large value will result in a least squares solution which may be unstable, while a small value may over smooth the solution due to excessive regularization [18,26,27,28]. Here, we set λ according to the method described in [28]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trick is not directly transposable to the migration technique. Finally, another advantage of migration approach is the easier possibility to use filtering and regularization techniques [13].…”
Section: Migration Tfm Methodsmentioning
confidence: 99%